Grants Expenditure and Capital Expenditure Pattern Analysis - Taufik Nugraha Suryana; Sri Mulyani (Journal of Accounting Auditing and Business, 2019)
The aim of this research to determine the Political Budget Cycle’s (PBC) patterns in grants expenditure and capital expenditure before, during, and after the regional election in Indonesia in 2012. The method used in this research is a mixed-method, where the first testing used simple regression (quantitative approach) then followed by content analysis (qualitative approach) for getting more finding from the data. Sample method used in this research is based on a purposive sampling method. The results showed that there were Political Budget Cyle’s patterns though there was no significant effect of Regional Election on Grants Expenditure and Capital Expenditure. The conclusion indicated that there were Political Budget Cycle’s patterns in Indonesia on Grants Expenditure and Capital Expenditure.